To simplify the expression \( x^{16} \cdot x^{16} \), we can use the property of exponents that states \( a^m \cdot a^n = a^{m+n} \).
Applying this property to the given expression:
\[ x^{16} \cdot x^{16} = x^{16+16} = x^{32} \]
Now, we need to determine which of the provided options is equivalent to \( x^{32} \).
Let's evaluate the options:
- \( \sqrt{x} = x^{1/2} \) (not equivalent)
- \( \sqrt[3]{x} = x^{1/3} \) (not equivalent)
- \( \sqrt[36]{x} = x^{1/36} \) (not equivalent)
- \( \frac{1}{\sqrt[3]{x}} = x^{-1/3} \) (not equivalent)
None of the provided options are equivalent to \( x^{32} \).
It appears there has been a misunderstanding in the options provided as none correspond to \( x^{32} \). If you have any additional context or specific instructions to follow, please let me know.